Influência da intensidade da corrida e do tempo de recuperação na cinemática, coordenação e regularidade dos membros inferiores durante a tarefa de agachamento unipodal em praticantes de corrida - Mariana Rodrigues Carvalho de Aquino (2023)
Background: Runners present high rates of musculoskeletal injuries that are related to the inability to resist and recover from the demand imposed by exercise and training routines. Different exercise intensities can induce different levels of fatigue and lead to changes in kinematics, coordination pattern, and regularity, which require time to recover. An imbalance between recovery time and the demands imposed by exercise can contribute to the development of injuries. The main objective of this study was to investigate the influence of running intensity and recovery time on lower limb kinematics, coordination pattern, and regularity during a single-leg squat task and the relationship with the injury occurrence in runners. Methods: Thirty healthy recreational runners performed a 60-second single-leg squat task on pre, post, 24 and 48 hours after running at moderate (60min, 65%VO2max) and high-intensity (4x15min, 85% VO2max) or rest (control). After six months of assessments, runners who were injured within this period were compared with non-injured runners. Joint kinematics (ankle, knee, and hip angles) and coordination pattern (relative phase between ankle-knee and knee-hip angles) were analyzed using mean cycle-normalized curves and regularity (Multiscale Entropy). ANOVA analyses were performed to verify interactions between protocols (moderate, high, control) and times (pre, post, post24, post48), and between protocols, times, and groups. Results: Increases in ankle-knee regularity (lower entropy) were observed after both running protocols. Additionally, the injured group presented a more regular movement pattern and required more time to recover than non-injured group. No differences were observed in the pre-test, after the control protocol, or when evaluating cycle-normalized mean curves of joints and coordination angles. Conclusion: Monitoring changes during a functional task can provide important early information about the individuals' ability to adapt and recover from training and exercise.